Dietary supplementation of Thai black rice bran extract and yeast beta-glucan protects the dextran sodium sulphate mediated colitis induced rat - Noppawat Pengkumsri (2018)
© The Royal Society of Chemistry. The present study was employed to evaluate the impact of black rice bran (BRB) extract, and yeast β-glucan (YBG) supplementation on a dextran sodium sulfate (DSS)-induced colitis rat model. Serum level antioxidant enzymes, cytokines, and histopathological changes were studied by spectrophotometric, ELISA, HPLC, and microscopic analysis. The preventive effect of RB + YBG combinational treatment for DSS-induced colitis in rat was greater than that of RB extract and YBG regarding serum antioxidant level. The elevated expression of the studied inflammatory cytokines (IL-6, IL-17, IFN-γ) was effectively more attenuated by RB + YBG combinational treatment than other tested interventions, which was accompanied by an increase in anti-inflammatory cytokines (IL-10, TGF-β). The histological study supported that RB + YBG supplementation improves the health status of DSS-induced colitis rats. The results suggested that the supplementation of RB + YBG was a potent alternative nutrient based therapeutic agent for colitis and to prevent the development of cancer.